2009
DOI: 10.1002/jgm.1311
|View full text |Cite
|
Sign up to set email alerts
|

Baculovirus is an efficient vector for the transduction of the eye: comparison of baculovirus‐ and adenovirus‐mediated intravitreal vascular endothelial growth factor D gene transfer in the rabbit eye

Abstract: The study suggests that baculoviruses are efficient vectors for ocular gene transfer, especially if deeper retinal layers need to be transduced. In addition, intravitreal VEGF-D gene transfer caused blood-retina barrier breakdown but not neovessel formation in the rabbit eye.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 38 publications
3
24
0
Order By: Relevance
“…Subretinal injections resulted in restricted transduction of retinal pigment epithelium (RPE) cells, whereas intravitreal injections led to gene expression in the corneal endothelium, RPE, lens and retina. Similarly, we demonstrated efficient transduction of retina, RPE and also photoreceptor cells after intravitreal injections to rabbit eye (Kinnunen et al, 2009). Three other studies have used intravitreal injection of baculovirus to rat eye to demonstrate the specificity of transgene expression from endothelial-and neuronal-specific promoters (Li et al, 2004(Li et al, , 2005Luz-Madrigal et al, 2007).…”
Section: Eyementioning
confidence: 73%
“…Subretinal injections resulted in restricted transduction of retinal pigment epithelium (RPE) cells, whereas intravitreal injections led to gene expression in the corneal endothelium, RPE, lens and retina. Similarly, we demonstrated efficient transduction of retina, RPE and also photoreceptor cells after intravitreal injections to rabbit eye (Kinnunen et al, 2009). Three other studies have used intravitreal injection of baculovirus to rat eye to demonstrate the specificity of transgene expression from endothelial-and neuronal-specific promoters (Li et al, 2004(Li et al, , 2005Luz-Madrigal et al, 2007).…”
Section: Eyementioning
confidence: 73%
“…Tani et al (28) demonstrated that vesicular stomatitis virus glycoproteinmodified baculovirus was able to transduce a reporter gene into the cerebral cortex and testes of mice by direct inoculation in vivo. Furthermore, intravitreal injection of baculovirus caused expression of vascular endothelial growth factor in the inner retina, photoreceptor cells, and retinal pigment epithelium cells of rabbit eye (10). In the present study, we have also evaluated the potential of live BacHA to transduce the intestinal epithelial cells of orally immunized mice.…”
Section: Discussionmentioning
confidence: 94%
“…Moreover, not only can the baculoviruses be easy and cheap to produce, they can be grown to high titers in cell cultures as well. Although baculovirus vectors have not been used thus far for shRNA delivery in vivo, but these have been successfully used for gene transfer into mouse brain and rabbit retina (Lehtolainen et al 2002;Kinnunen et al 2009). …”
Section: Baculoviral Vectorsmentioning
confidence: 99%